THE CASE OF CUTANEOUS ANTHRAX - Ts. Doychinova; G. Gancheva; D. Shalamanov; R. Nenova; S. Ivanova; J. Petkov (Медицинский вестник Юга России, 2013)
A case of the disease in the skin form of anthrax which was held with discrete toksoinfektsionnym syndrome, but with characteristic skin manifestations, etiology, and ended proven recovery.